Formulation and characterization of polymeric nanoparticle of Rivastigmine for effective management of Alzheimer’s disease - Faisal Imam; Sayantan Mukhopadhyay; Preeti Kothiyal; Samiyah Alshehri; Khalid Saad Alharbi; Muhammad Afzal; Muzaffar Iqbal; Mohammad Rashid Khan; Md. Khalid Anwer; Abdulrazaq Ahmed Hattab Alanazi; Ali Ghanem Alqahtani; Mohammed Abdullah Alhamamah (Saudi Pharmaceutical Journal, 2024)
Memory loss or dementia is a progressive disorder, and one of its common forms is Alzheimer’s disease (AD), effecting mostly middle aged and older adults. In the present study, we developed Rivastigmine (RIV) nanoparticles using poly(lactic-co-glycolic acid) (RIV-loaded PLGA NPs) and polyvinyl alcohol (PVA). The prepared RIV-PLGA nanoparticles was evaluated for the management of Alzheimer's disease (AD). The nanoparticles were prepared by the slightly modified nano-precipitation technique. The developed formulations were evaluated for particle size, zeta potential (ZP), polydispersibility index (PDI) and surface morphology and drug content. The experimental result revealed that prepared RIV-loaded PLGA NPs (F1) was optimized having particle size (61.2 ± 4.6 nm), PDI (0.292), ZP (−11.2 ± 1.2). SEM study confirms the prepared nanoparticles depicted non-aggregated as well smooth surface particles without any fracture. This formulation (F1) was further assessed for in vivo studies on animal model. A pharmacological screening on an animal model of Alzheimer's disease revealed that RIV-loaded PLGA NPs formulations treat CNS disorders like Alzheimer's effectively. In addition to that, an in-vivo brain cholinesterase estimation study found that, animals treated with optimized formulation significantly (p < 0.01) reduced brain cholinesterase activity when compared to scopolamine-treated animals. According to the above results, it can be concluded that RIV-loaded PLGA NPs are ideal carriers for delivering the drug at a specific target site in the brain, thus may treat Alzheimer's disease efficiently and improve patient compliance.